A case for reform of tax expenditures applicable to agriculture in Australia. (21st December 2006) - Gumley, Wayne
This paper considers the need for ecological fiscal reform to address chronic land degradation problems in rural Australia. The paper reviews the range of regulatory strategies available to deal with this problem and notes that market-based approaches are strongly favoured by the Australian government. However the author notes that various pre-existing subsidies and taxation concessions may undermine market based approaches. This paper considers the range of subsidies applicable to agriculture in Australia and notes particular problems in the scrutiny of tax expenditures, which represent an increasing proportion of total government outlays, but are not subject to the same review processes as direct government payments. The author concludes that future economic and ecological harm can be mitigated by some specific reforms to the procedures for approval and review of tax expenditures in national budget processes.